Does investor identity matter? An empirical examination of investments by venture capital funds and hedge funds in PIPEs - Dai, Na (Journal of Corporate Finance, 2007)
I examine the emerging phenomenon of PIPEs (private investments in public equity) invested by venture capital funds (VCs) and hedge funds (HFs) and analyze whether and how these investors add value to firms by comparing a sample of 113 VC-invested PIPEs to a sample of 397 PIPEs with HFs. I find that VCs gain substantial ownership, request board seats, and often keep their stake after the PIPEs. In contrast, HFs rarely join the board of directors and typically cash out their positions shortly after the PIPE. The stock performance of VC-invested firms is significantly better than HF-invested firms both in the short run and in the long run. The positive valuation effect of having VCs as PIPE investors appears to be a certification effect rather than a monitoring effect. A key implication from these findings is that investor identity matters.